Insider resistance : understanding refugee protest against immigration detention in Australia, 1999 – 2005 - Fiske, Lucy (Curtin University, 2012)
Protests by detainees in Australia’s immigration detention centres made regular headline news between 1999 and 2005. Journalists interviewed government ministers, senior departmental officials, refugee advocates, mental health experts and many others. Only rarely were detainees able to speak directly for themselves and explain their own actions. The primary task of this research has been to reunite the words of former detainees with their actions. Through interviews with former detainees, alongside a broad range of secondary sources, such as government media releases, news reports, inquiry reports and court transcripts, this thesis presents an alternative record of protests and other events inside detention centres. Detainees’ thoughts, words and actions are outlined in thematic chapters addressing human rights and the human subject of human rights, power and resistance in detention, escapes and breakouts, hunger strike and riot.Testimony from former detainees confirms that despair was widespread within immigration detention centres. However, it also reveals a discursive struggle for reinstatement as rights bearing human beings. Detainees engaged in collective and individual critique of their position within Australian and global politics, of the flow of power within detention centres, of their public representation and of the risks and potential benefits of possible protest actions. Interviews with former detainees revealed a diverse political consciousness and both strategic and principled thinking which drove protest action. The interviews also uncovered important insights into the interplay of reason and emotion in resistance undertaken by those directly experiencing injustice.Hannah Arendt argued that becoming a refugee entails a loss of ‘the right to have rights,’ which amounts to an expulsion, not only from a political community, but from humanity itself. In this research, the work of Hannah Arendt is used to expose the ways in which Australia’s regime for responding to asylum seekers who arrive by boat strips people of their status as ‘full’ human beings and is therefore fundamentally dehumanising. The words and deeds of detainees however, extend Arendt’s work on human rights and support the argument that certain characteristics of ‘naked humanity,’ including thought, speech and action, cannot be removed and that detainees remained discursive agents throughout their period of detention. Detainees used critical and strategic understandings of power to engage in a struggle for restoration as rights bearing human beings.